2015
DOI: 10.1016/j.comppsych.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Chinese rural young suicides: Who did not have a strong intent to die

Abstract: Background In exploration of the risk factors of the Chinese rural young suicide, previous researchers found low prevalence of mental problems, high degree of impulsivity, and great proportion of lethal pesticide consumption. It noticed that some of the young suicides in rural China did not intend to die from the suicidal behavior which was only instrumentally used for certain gains. Aims This study aims to look into the characteristics of those young suicides who did not really intend to die and compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“… 49 Previous studies have also suggested that impulsivity contributed to suicide death in rural China. 21 It implies that some attempters do not want to die by suicide which is consistent with our assumption.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 49 Previous studies have also suggested that impulsivity contributed to suicide death in rural China. 21 It implies that some attempters do not want to die by suicide which is consistent with our assumption.…”
Section: Discussionsupporting
confidence: 86%
“…However, the choice of the suicide means may be caused by the higher level of violence for men compared with women, and we cannot conclude that men may have a higher intent to die. 21 In the current study, we also examined the relationship between physical disease, family suicide history and suicide intent. Both of them were not associated with suicide intent.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, suicide attempters with MDD were willing to write suicide notes. In addition, one study that examined impulsivity and suicide ideation reported that suicide attempts with low intent were associated with impulsivity [ 39 ], which is consistent with our findings. Finally, in our study, we found that the quality of life of the MDD group was lower than that of the no psychiatric diagnosis group.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with mental illnesses were more likely to die [ 35 ]. Some previous studies supported the view that mental illness, especially major depressive disorder [ 36 38 ], is an independent risk factor for suicide with high suicide intent [ 33 , 39 , 40 ] and found that self-harm of MDD patients was more motivated by depressive symptoms than self-harm in patients with no psychiatric diagnosis [ 22 ]. Second, we found that the suicide attempters with no psychiatric diagnosis had significantly more self-rescue and were more impulsive than the suicide attempters with MDD.…”
Section: Discussionmentioning
confidence: 83%
“…Due to the markedly high suicide rates in Chinese rural young women in the 1990 s, much research and public attention was paid to suicide of young adults333435 while ES has been neglected in China. To the best of our knowledge, this is the first study that reports long-term trends of ESRs based on China’s largest regular national mortality monitoring system during a long period spanning from 1987 to 2014.…”
Section: Discussionmentioning
confidence: 99%